Reviews - Philip Barker; Geoff Goolnik; Harish Ravat; Gordon Ritchie; John Robertson; Beryl Starr; Paul van Schaik; Janice Whatley (Association for Learning Technology, 1999)
For many people, the terms 'multimedia' and 'Internet' are now quite familiar expressions that trigger many different thought patterns and associations. Very often, the associations that we make depend critically upon our backgrounds and prior experiences - particularly within hybrid areas such as multimedia, computing and information technology. Glossaries and dictionaries are therefore useful tools for providing a common level of meaning for the technical terms and jargon that we use in particular subject domains. This particular book offers a guide to the terminology associated with the Internet and multimedia applications.